Quality Parameters and Fermentation Characteristics of Ensiled Water Hyacinth(Eichhornia crassipes) - Hundal, J.S.; Singh, Digvijay; Ansal, Meera D.; Chahal, Udeybir Singh; Kaur, Vaneet Inder; Sharma, Amit (Indian Journal of Animal Nutrition, 2025)
The present study was conducted to explore the nutritional potential of wilted Water Hyacinth silage as an unconventional feed resource. A total of seven Water hyacinth silage; six were wilted viz. T1 (Eichhoria 75%+ rice straw 16%+ molasses 4%) T2 (Eichhoria 75%+ rice straw 15.5+ molasses 4%+Urea 0.5%); T3 (Eichhoria 75%+ rice straw 10%+ molasses 4%+ wheat bran 6%); T4 (Eichhoria 75%+ rice straw 10%+ molasses 4%+ moringa 6%); T5 (Eichhoria 65 %+ rice straw 25%+ molasses 4%); T6 (Eichhoria 65% + rice straw 25%+ molasses 4% and Urea 1%) and one without wilting T7 (Eichhoria 95%) were prepared. The addition of 10% Rice straw + 6 % WB or 6% moringa (T3 and T4) increased (P<0.001) the CP, DM intake (%BW), digestible DM (%), TDN (%), RFV and RFQ. The fibre content NDF, ADF and cellulose levels were reduced (P<0.001) in T-3 and T-4 silage as compared to treatments that added 16 % RS (T1 and T2) and 25% RS (T5 and T6). The NGP (ml/g) was reduced (P<0.05) in T-3 and T-4, however, OMD (%) and ME (Kcal/g), NDFD%, PF and MBP levels were increased (P<0.001). The WH silage (T7) alone was of poor quality with undesirable odor and colour. It can be concluded that wilted water hyacinth silage can be improved with the addition of rice straw (10%) and wheat bran (6%) or moringa oleifera (6%) and molasses (4%) to use as an unconventional feed resource in animal feed.